Peran Pondok Pesantren Sebagai Lembaga Pengembangan Dakwah - irfan mujahidin (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2021)
This present study aims at identifying the role of Islamic boarding schools as da’wah institution. Islamic boarding schools in fact provided the process of teaching, educating, and exemplaring values every second and minute and every hour of the clerics to his students. Educational in islamic boarding school aims to forge themselves into an independent person and to develop a spirit of togetherness, which includes the attitude of mutual assistance, solidarity and brotherhood among the students. In terms of individual character development, schools teach thrift and simple life away from the consumptive nature. The role of Islamic boarding schools was not only as educational institutions but also it took a role as a religious institution operated as a basis in the process of changing social in society. In there, the basics of science are taught for dakwah, so the students have to do da’wah when they will enter to the society. Thus, Islamic boarding schools as an Islamic educational institution owned by the community is really potential for the Establishing of man power, potential for the creation of intelligence and well-being of the nation. Not a bit of Dakwah that could be done through schools, good Dakwah that convey the teachings of Islam, as well as preaching about the life and development of the Ummah.